Higher serotonin transporter occupancy after multiple dose administration of escitalopram compared to citalopram: an [123I]ADAM SPECT study - Klein, Nikolas; Sacher, Julia; Geiss-Granadia, Thomas; Mossaheb, Nilufar; Attarbaschi, Trawat; Lanzenberger, Rupert; Spindelegger, Christoph; Holik, Alexander; Asenbaum, Susanne; Dudczak, Robert; Tauscher, Johannes; Kasper, Siegfried (Psychopharmacologia, 2007)
Previous studies have investigated the occupancy of the serotonin reuptake transporter (SERT) after clinical doses of citalopram and other selective serotonin reuptake inhibitors. In the present study, the occupancies of SERT after multiple doses of escitalopram and citalopram were compared using the radioligand [(123)I]ADAM and single photon emission computed tomography (SPECT). Fifteen healthy subjects received escitalopram 10 mg/day (n = 6) or citalopram 20 mg/day (n = 9) for a total of 10 days. SERT occupancies in midbrain were determined with SPECT and [(123)I]ADAM at three different time points: at baseline (no medication) and at 6 and 54 h after last drug intake. At 6 h after the last dose, mean SERT occupancies were 81.5 +/- 5.4% (mean+/-SD) for escitalopram and 64.0 +/- 12.7% for citalopram (p < 0.01). At 54 h after the last dose, mean SERT occupancies were 63.3 +/- 12.1% for escitalopram and 49.0 +/- 11.7% for citalopram (p < 0.05). The plasma concentrations of the S-enantiomer were of the same magnitude in both substances. For both drugs, the elimination rate of the S-enantiomer in plasma was markedly higher than the occupancy decline rate in the midbrain. The significantly higher occupancy of SERT after multiple doses of escitalopram compared to citalopram indicates an increased inhibition of SERT by escitalopram. The results can also be explained by an attenuating effect of R-citalopram on the occupancy of S-citalopram at the SERT.